2010
DOI: 10.1007/s12185-010-0652-3
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet effect of once- or twice-daily aspirin dosage in stable coronary artery disease patients with diabetes

Abstract: The aim of this pilot study was to compare the effect of two different regimens of aspirin dosage on platelet of coronary artery disease (CAD) diabetic patients. Twenty-five CAD diabetic patients were included. Initially, all patients received aspirin 100 mg/day for 10 days. At day 10, aspirin antiplatelet effect was determined by measuring the collagen/epinephrine closure time (CT) 2 h after the last aspirin dosage and the next morning at 8 a.m.. The aspirin regimen was modified to 100 mg twice daily for pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…aspirin resistance), but data are somewhat sparse and at times contradictory. For example, increasing the aspirin dose (from 30 mg/ day to up to 320 mg/day) significantly reduced platelet aggregation in patients with diabetes and CAD in most, [89][90][91] but not all, [61,92] studies and production of TXB 2 or 2,3-dinor-TXB 2 (markers of actual COX inhibition) has been reported to decrease [61,91,92] or remain unaltered. [90] Although increasing the daily dose of aspirin may augment the antiplatelet effect of aspirin, [18,21] it also decreases prostaglandin production [18] and increases the potential risk for adverse effects (e.g.…”
Section: Aspirin: Antiplatelet Effects and Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…aspirin resistance), but data are somewhat sparse and at times contradictory. For example, increasing the aspirin dose (from 30 mg/ day to up to 320 mg/day) significantly reduced platelet aggregation in patients with diabetes and CAD in most, [89][90][91] but not all, [61,92] studies and production of TXB 2 or 2,3-dinor-TXB 2 (markers of actual COX inhibition) has been reported to decrease [61,91,92] or remain unaltered. [90] Although increasing the daily dose of aspirin may augment the antiplatelet effect of aspirin, [18,21] it also decreases prostaglandin production [18] and increases the potential risk for adverse effects (e.g.…”
Section: Aspirin: Antiplatelet Effects and Pharmacokineticsmentioning
confidence: 99%
“…In patients with diabetes and CAD, twice-daily dosing of aspirin 100 mg (total dose, 200 mg/day) or 75 mg (total dose, 150 mg/day) improved platelet aggregation compared with once-daily administration of aspirin 100 or 75 mg/day, respectively. [89,94] Twicedaily administration of aspirin 100 mg (total dose, 200 mg/day) also slowed recovery of TXB 2 concentrations during a 12-to 24-h period compared with oncedaily aspirin 100 mg in patients with diabetes and prior vascular disease. However, improved aspirin responsiveness has not been observed with twice-daily dosing of higher doses [i.e.…”
Section: Aspirin: Antiplatelet Effects and Pharmacokineticsmentioning
confidence: 99%
“…[39, 38] Addad and colleagues reported that aspirin 100 mg twice daily significantly reduced HPR compared with aspirin 100 mg once daily. [76] Spectre and colleagues further observed that 75 mg twice daily was more effective in decreasing aspirin resistance on aggregometric testing compared both, with 75mg and with 320 mg once daily. Although this was a small study, the twice daily regimen was more efficacious in patients with more reticulated platelets at baseline.…”
Section: Aspirin Resistance In Diabetesmentioning
confidence: 99%
“…7,8 By dosing twice instead of once daily, they hypothesized that lower platelet reactivity would result through improved inhibition of juvenile platelets. In a previous study by Addad et al, 11 patients with DM treated with twice-daily dosing compared to once-daily dosing had lower platelet reactivity. Capodanno et al administered aspirin at the following weekly doses in succession to 20 patients: 81 mg QD, 81 mg BID, 162 mg QD, 162 mg BID, and 325 mg QD.…”
Section: Article See P 180mentioning
confidence: 81%